Critique to the intervention in the archaeological site of the Bodega y Quadra house - Arciga Soto, Rolando (2016)
The intervention of the Bodega y Quadra House in the Historic Center of Lima-Perú is the only contemporary case of a site museum in this part of the city where an archaeological site of the colonial era can be observed. The intervention has many key aspects, among which some are particularly salient, such as the political decision of the Municipalidad Metropolitana de Lima to create the museum; its favorable location in the heart of the historic city center itself, which is consistent with the preservation or environmental conservation; and the preservation of the relationship between the archeological site and its pieces via the site museum, which is the most appropriate use of the monument as indicated by the theory of objective restoration. This is an intervention of the archaeological area that by and large was respectful of the principles of contemporary scientific restoration.